ANALYSIS OF THE APPLICATION OF SUSTAINABLE ECONOMY TO FOSSIL ENERGY CONSUMPTION TO THE ENVIRONMENT - Istiningsih, Nurmayani; Zainuddin , Zulkifli (Sekolah Tinggi Ilmu Ekonomi Ganesha, 2024)
The number of the world's population continues to increase every year in line with the increasing rate of economic growth, the rate of population growth, and the rapid development of the industrial sector. So that an increase in energy demand is inevitable. Human energy needs are obtained from the conversion of fossil energy sources, either directly or indirectly, which can have a negative impact on the environment and the health of living things and inefficiencies. The burning of fossil energy sources causes air pollution (acid rain, smog and global warming) where acid rain causes soil and waters (lakes and rivers) to become acidic. For agriculture and forests, the acidity of the soil will affect the growth of crop production. In the waters, acid rain will cause disturbances for living things in it. So that the number of human activities in increasing economic growth becomes more and has an impact on the environment, especially in the use of energy sources for the needs of households, industries and so on with the increasing use of fossil energy causing various problems, especially for the environment which uses a lot of fossil energy. This study generally aims to (1) Determine the form of implementation of sustainable development policies (2) Factors that inhibit and support the implementation of sustainable development policies. This research was conducted with descriptive qualitative research. Where in this study using triangulation using an inductive method, the results of qualitative research emphasize more on meaning than generalization. With the results of the study, fossil energy consumption has a big impact on the environment, especially through greenhouse gas (GHG) emissions. Sustainable economics emphasizes the importance of meeting today's needs without sacrificing the capabilities of future generations. And with public awareness of the impact of fossil energy consumption is critical in the transition to a sustainable economy. And although there are many opportunities, there are several challenges that need to be faced in implementing a sustainable economy on fossil energy consumption. So the researcher suggested increasing education and awareness and bureaucratic reform.